2019
DOI: 10.6004/jnccn.2018.7077
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Tumor Characteristics to Maximize 21-Gene Assay Utility: A Cost-Effectiveness Analysis

Abstract: Background: Literature suggests that Oncotype DX (ODX) is cost-effective. These studies, however, tend to ignore clinical characteristics and have not incorporated population-based data regarding the distribution of ODX results across different clinical risk groups. Accordingly, this study assessed the cost-effectiveness of ODX across strata of clinical risk groups using population-based ODX data. Methods: We created state-transition models to calculate costs and quality-adjusted life years (QALYs) gained over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…Literature reported that only a quarter to a third of the eligible patients in the United States had this assay performed [7,12], and in developing countries, certain controversy remained regarding the applicability of this testing [13]. On another hand, cost-effectiveness analysis demonstrated that the 21-gene RS testing was only associated with lower cost in patients with clinical high-risk [14,15]. Thus, a surrogate for the 21-gene RS testing is needed for those who have no access to this assay, as well as to relieve the heavy financial burden of patients for whom the testing is not cost-efficient [16].…”
Section: Discussionmentioning
confidence: 99%
“…Literature reported that only a quarter to a third of the eligible patients in the United States had this assay performed [7,12], and in developing countries, certain controversy remained regarding the applicability of this testing [13]. On another hand, cost-effectiveness analysis demonstrated that the 21-gene RS testing was only associated with lower cost in patients with clinical high-risk [14,15]. Thus, a surrogate for the 21-gene RS testing is needed for those who have no access to this assay, as well as to relieve the heavy financial burden of patients for whom the testing is not cost-efficient [16].…”
Section: Discussionmentioning
confidence: 99%
“…Actually, Oncotype DX® is based, among others, on the expression of 5 genes related to proliferation (namely MKI67, STK15, Survivin, CCNB1 and MYBL2), and the association between both RS and single gene expression with the Ki67 IHC levels has previously been addressed. [20][21][22][23] Since use of Oncotype DX® in routine practice requires important financial resources and its cost-effectiveness has been questioned in the literature, 24,25 especially for low-risk BC patients, Ki67-PS can possibly provide additional information with an inferior burden on National Health System budget.…”
Section: Discussionmentioning
confidence: 99%
“…1), we simulated a hypothetical cohort of 60-year-old women, stratified by PREDICT risk, and estimated costs and quality-adjusted life years (QALYs) associated with the 2 strategies over a lifetime horizon. 28 We employed a US-payer perspective and discounted costs and QALYs by 3%. 29 Costs were expressed in 2015 US dollars ($), and the health-related quality-of-life adjustments (ie, the "utility weights") used to estimate QALYs were taken from the literature (see Appendix Table 1 in Supplemental Materials found at https://doi.org/10.1016/j.jval.2019.05.…”
Section: Decision-analytic Modelmentioning
confidence: 99%
“…The AML and CHF health states represent long-term toxicities from chemotherapy. In line with the model used by the National Institute for Health and Care Excellence in the UK, 28,30 this Markov model assumes that a proportion of patients with distant recurrence have previously developed a local recurrence. The model also includes absorbing health states for death from different causes, including breast cancer (BC), AML, CHF, and other causes.…”
Section: Decision-analytic Modelmentioning
confidence: 99%
See 1 more Smart Citation